ISO LWS far-infrared observations of jupiter and saturn - Oldham, P; Griffin, M; Davis, G; Encrenaz, T; De Graauw, T; Irwin, P; Swinyard, B; Naylor, D; Burgdorf, M (1997)
Portions of the far-infrared spectra of Jupiter and Saturn measured in grating mode with the ISO Long Wavelength Spectrometer (LWS) are presented. The observed Jovian spectrum between 55 and 90 μm is compared to an atmospheric radiative transfer model using expected values for the constituent vertical concentration profiles. Rotational transitions of ammonia are responsible for the absorption features observed against the hydrogen continuum emission. There is good agreement between the model and data for an ammonia mole fraction of 2×10-4 constrained by saturation up to a 75 mbar cut-off, above which it is assumed all the ammonia is destroyed by ultraviolet radiation. Three sections of the saturnian spectrum are compared to synthetic spectra and absorption features due to methane are identified. The mole fraction of methane is constrained between 0.7-1.5 10-3.